Photoactive Polyoxometalate/DASA Covalent Hybrids for Photopolymerization in the Visible Range. Issue 63 (9th October 2019) - Boulmier, Amandine; Haouas, Mohamed; Tomane, Somia; Michely, Laurent; Dolbecq, Anne; Vallée, Anne; Brezová, Vlasta; Versace, Davy‐Louis; Mialane, Pierre; Oms, Olivier
Abstract: The synthesis of TBA‐DASA‐POM‐DASA, the first photoactive covalent hybrid polyoxometalate (POM) incorporating a donor–acceptor Stenhouse adduct (DASA) reverse photochrome, is presented. It has been evidenced that in solution the equilibrium between the colorless cyclopentenone and the highly colored triene conformers is strongly dependent not only on the nature of the solvent but also the countercations, allowing to tune its optical properties. This complex has been further associated to photochromic spironaphtoxazine cations, resulting in a material which can be activated by two distinct optical stimuli. Moreover, when combined with N ‐methyldiethanolamine, TBA‐DASA‐POM‐DASA constitutes a performing photoinitiating system for polyethylene glycol diacrylate polymerization and under visible light irradiation, a promising result in a domain scarcely developed in POM chemistry. Abstract : POMs and DASA : the first compound associating in a single molecule a polyoxometalate and a reverse photochrome is reported. It can be activated via two orthogonal optical stimuli when ionically associated to an organic photochrome. Furthermore, its ability to act as a photoinitiator in free‐radical polymerization process under visible light is demonstrated.